2019
DOI: 10.29252/ajcm.26.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Gabapentin and Evening Primrose Oil on Peripheral Neuropathy Pain in Patients with Type 2 Diabetes

Abstract: Background and Objective: Neuropathic pain is one of the common, important, and irritating complications in diabetes. Despite the importance of this pain, there is still no effective treatment for that. The aim of this study was to determine the effect of evening primrose oil and gabapentin on neuropathic pain in patients with type 2 diabetes. Materials and Methods: This triple-blind clinical trial was performed on 70 patients with diabetic neuropathy who obtained score 2 from the Michigan Questionnaire and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In a study to determine the effect of EPO on cervical dilatation and pain intensity before and during hysterosalpingography, the intervention group reported less pain intensity than the control group when using a cervical tenaculum and injecting contrast material [ 25 ]. Also, studies have indicated the effect of EPO on reducing post-appendectomy pain [ 26 ], neuropathic pain in type 2 diabetic patients [ 27 ], and mastalgia [ 28 , 29 ]. On the other hand, a study aimed at determining the effect of vaginal EPO administration on cervical ripening in primiparous women with post-term pregnancies showed that the average pain intensity in the control and intervention groups did not have a statistically significant difference [ 12 ], which was not consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study to determine the effect of EPO on cervical dilatation and pain intensity before and during hysterosalpingography, the intervention group reported less pain intensity than the control group when using a cervical tenaculum and injecting contrast material [ 25 ]. Also, studies have indicated the effect of EPO on reducing post-appendectomy pain [ 26 ], neuropathic pain in type 2 diabetic patients [ 27 ], and mastalgia [ 28 , 29 ]. On the other hand, a study aimed at determining the effect of vaginal EPO administration on cervical ripening in primiparous women with post-term pregnancies showed that the average pain intensity in the control and intervention groups did not have a statistically significant difference [ 12 ], which was not consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in addition to their side effects, the effectiveness of pain relievers (oral solution) like pregabalin and duloxetine is varied [ 31 ]. Therefore, considering the high degree of DPN and the limited known treatments for managing this illness, it is essential to use medications with acceptable efficiency and effectiveness [ 32 ]. According to the results of previous studies, clonidine is likely to alleviate neuropathic pain when used topically on the painful area [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%